Treatment of bladder cancer: present and perspectives - Skoneczna, Iwona; Milecki, Piotr; Nawrocki, Sergiusz; Skacel, Tomasz; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
Bladder cancer is one of the most frequent tumours of the urinary tract in Poland. The superficial disease is treated with transurethral resections and additionally with local immunotherapy or chemotherapy with good results. However, there is a considerable fraction of BCG-refractory tumours (30%) and progression to muscle-invasive cancer. New approaches such as BCG combined with low-dose interferon or recombinant BCG strains are promising but need to be explored in prospective clinical trials. Better understanding of tumour biology and immunology probably will enable to distinguish patients with a high risk of progressive disease and to tailor further therapy options. The cornerstone of muscle invasive tumours treatment is radical cystectomy. The neoadjuvant chemotherapy is a promising option, especially in tumours invading deeply bladder wall or infiltrating surrounding organs but requires confirmations of early results in phase III trials before introduction as a standard treatment. Combined chemotherapy and modern 3-D conformal radiotherapy enable to preserve the organ and function of the bladder (bladder conserving therapy) and is intensively studied in ongoing trials. another issue which is intensively studied is a molecular characterisation of individual tumours. It might help to choose for particular patient the bladder conserving therapy or cystectomy in the near future. The use of neoadjuvant or adjuvant chemotherapy with surgery or radiotherapy is still controversial, however the results of recent trials of neoadjuvant chemotherapy in locally advanced bladder tumours convinced some leading centres to implement neoadjuvant chemotherapy in selected groups of patients (e. g. M. D. Anderson – Houston, USA; MSKCC – New York). By far, four-drug regimen – MVAC was widely used in metastatic advanced disease. Recently has been evaluated in randomised trial the combination of gemcitabine and cisplatin (GC). This regimen is equally effective as MVAC but less toxic. At present a new chemotherapies like gemcitabine, taxanes and new-class drugs interfering with signal transduction are tested in clinical trials. Individualization of established and investigational treatment options based on molecular tumour characteristics, such as p53 status is probably the future of bladder cancer pharmacotherapy.